Pengaruh Program Pelatihan Dan Pengembangan Sumber Daya Manusia Terhadap Peningkatan Kemampuan dan Kinerja Karyawan PT. Bank Syariah Mandiri - Retnilasari, Elsa; Putra, Purnama (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2019)
The Effect of Training and Human Resources Development Programs on the Improvement of theCapability and Performance of the Employees of PT. Bank Syariah Mandiri. The purpose of this studywas to analyze how much influence the variables of the training and development program on thevariable of employee capacity improvement partially or individually and which variable had the mostinfluence on PT. Bank Syariah Mandiri, to analyze how much influence the training and developmentprogram variables have on the combined ability of employees at PT. Bank Syariah Mandiri, to analyzehow much influence the training, development and capacity improvement variables have on employeeperformance variables at PT. Bank Syariah Mandiri, to analyze how much influence the trainingand development variables have on employee performance variables through capacity building atPT. Bank Syariah Mandiri. This type of research is a quantitative descriptive study with a two-pathequation approach. The object of research chosen in this study is PT. Bank Syariah Mandiri. The typeof data used is primary and secondary data. Data collection techniques are done by questionnaire andobservation. The instrument used in this study was the Likert scale. The research variables use theconcept of independent variables namely training and development and the concept of the dependentvariable is the increase in employee ability and performance. The results of this study indicate thatthe training and development variables partially or individually to increase ability have a significanteffect. Of the two variables, the biggest influence is the development variable. The training anddevelopment variables combined to increase ability have a significant effect. And the influence of othervariables outside the model is 0.561. On the training variable, development, combined capabilityimprovement on employee performance has a significant effect. And the influence of other variablesoutside the model is 0.258.